Tinjauan Teoritis Psikologi terhadap Anak yang Menjadi Korban Kekerasan Seksual - Ni Made Swandari; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
At this time the protection of children who are victims of sexual violence must be treated intensively enough, this is due to previously experienced events resulting in severe injuries to the child's physical and mental. As for the formulation of the problem in this thesis, which is how to prosecute psychologist law against children as victims of criminal acts of sexual violence? And how is the legal protection to children victims of sexual violence accompanied by psychologists?? The method used is the normative method with the study of literature from primary legal materials and secondary. The conclusion of the problem formulation that refers to the provisions of Article 69 of the Child Protection Act, namely the letters "C and D" can be understood by the provisions of the Law can be used as a juridical basis of legal psychology as a form of special protection to ensure psychological victims of sexual violence crimes. Protection efforts at every level of examination ranging from investigation to judge's verdict, provision of social rehabilitation, psychosocial assistance, psychosocial rehabilitation and psychological rehabilitation as a form of protection provided by the Law so as to fulfill the sense of protection by the victim's child.